Early Early Breastfeeding Initiation (IMD) and Upper Arm Circumference (LILA) of Pregnant Women with the Incidence of Stunting in Takalar District - Sukmawati, Sukmawati; Yusnita, Yusnita; Zakaria, Zakaria; Chaerunnimah, Chaerunnimah (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
The results of the 2023 Indonesian Health Survey (SKI) showed that the prevalence of stunting in Indonesia reached 12.9% and severe stunting was 5.4%, South Sulawesi Province had a prevalence of stunting of 17.2% and severe stunting of 6.3%. Takalar Regency had a prevalence of stunting of 35.4% which is still above the WHO cut-off of 20%. One of the gold standards for providing infant feeding is Early Initiation of Breastfeeding (IMD). The purpose of the study was to determine the relationship between Early Initiation of Breastfeeding and the upper arm circumference of pregnant women with the incidence of stunting. This study is an observational study that is analytical in nature with a retrospective case-control approach. The study was conducted in Bontokadatto Village, Takalar Regency from July 2023 to March 2024. The sample was all toddlers who experienced stunting as many as 20 people as cases, the control was 20 toddlers who did not experience stunting. The statistical test used was the chi square test. The results showed that there was no significant relationship between IMD and the incidence of stunting in toddlers with a p-value of 0.27 (p-value> 0.05). There was no significant relationship between the upper arm circumference of pregnant women and the incidence of stunting in toddlers with a p-value of 0.72 (p-value> 0.05) in Takalar Regency. IMD is a risk factor for stunting in toddlers with an OR value of 3.05 (OR> 1) and maternal LILA during pregnancy is a protective factor for stunting with an OR value of 0.58 (OR <1). These findings provide new insights into understanding the factors that influence stunting, and their implications for maternal and child health policies. To mothers and health workers to provide early initiation of breastfeeding in newborns. Keywords : Toddlers, IMD, LILA, Stunting